Potential Antibacterial Agents: Part VI- Synthesis and Structure Elucidation of Schiff Bases Derived from Hydralazine - Sarfaraz, Tahira B.; Sultana, Naheed; Nelofar, Aisha; Hussain, Shaheen A. (Biological Sciences - PJSIR, 2007)
Synthesis of h ydrazones (Schiff bases) of an antihypertensive drug, hydra lazi ne was carried out. The study afforded the h itherto u nrepo rted 1 -[4-ch l orobenzyl i dene]-hyd razi nophtha l azi ne (111-a ), 1 -[ben zyl ide ne] h ydrazinophthal azi ne ( I 11-b ) , 1 -[4-n i trobenzyl i dene]-hydrazi nophthal azi ne (I II-c ), 1 -[2-n i trobenzyl i dene] hydrazi nophthalazi ne (III-d), 3-[4-chlorophenyl]-s-triazolo [3-4-a] phthalazine (IV-a) and 3-phenyl-s-triazolo [3-4-a] phthalazi ne (IV-b). The structu res of these compounds were established usi ng spectroscopic techniques i.e. [R, UV, 'HN MR, EIMS, FD and HR MS. Antibacterial activity of the drugs was eval uated.